2014
DOI: 10.1186/1471-2202-15-110
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles in multiple sclerosis and clinically isolated syndrome: effect on endothelial barrier function

Abstract: BackgroundCell-derived microparticles are secreted in response to cell damage or dysfunction. Endothelial and platelet dysfunction are thought to contribute to the development of multiple sclerosis (MS). Our aim here is, first, to compare the presence of microparticles of endothelial and platelet origin in plasma from patients with different clinical forms of MS and with clinically isolated syndrome. Second, to investigate the effect of microparticles on endothelial barrier function.ResultsPlatelet-poor plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 46 publications
3
73
2
Order By: Relevance
“…Several studies have demonstrated the presence of pro-inflammatory EVs at the site of inflammation in RA (Berckmans et al, 2002 ; Song et al, 2005 ), MS (Marcos-Ramiro et al, 2014 ; Sáenz-Cuesta et al, 2014a , b ), and inflammatory bowel disease (IBD; Mitsuhashi et al, 2016 ). MVs (Lindemann et al, 2001 ; MacKenzie et al, 2001 ) and exosomes (Qu et al, 2007 ) from several different cells are transporters of the strongly pro-inflammatory IL-1β, and membrane-bound TNF (mTNF) was found on synovial fibroblast exosomes from RA patients, but not from (non-autoimmune) osteoarthritis patients (Zhang et al, 2006 ).…”
Section: Lung Evs In Non-pulmonary Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated the presence of pro-inflammatory EVs at the site of inflammation in RA (Berckmans et al, 2002 ; Song et al, 2005 ), MS (Marcos-Ramiro et al, 2014 ; Sáenz-Cuesta et al, 2014a , b ), and inflammatory bowel disease (IBD; Mitsuhashi et al, 2016 ). MVs (Lindemann et al, 2001 ; MacKenzie et al, 2001 ) and exosomes (Qu et al, 2007 ) from several different cells are transporters of the strongly pro-inflammatory IL-1β, and membrane-bound TNF (mTNF) was found on synovial fibroblast exosomes from RA patients, but not from (non-autoimmune) osteoarthritis patients (Zhang et al, 2006 ).…”
Section: Lung Evs In Non-pulmonary Disordersmentioning
confidence: 99%
“…MS patients have increased serum levels of platelet MVs, which also correlate with clinical subtype (Sáenz-Cuesta et al, 2014a ). MVs from MS patients disrupted endothelial barriers in vitro (Marcos-Ramiro et al, 2014 ), and EVs have been suggested to contribute to MS by degrading the blood brain barrier, increasing endothelial activation and promoting neural inflammation (Sáenz-Cuesta et al, 2014b ). Fas ligand (FasL)-induced apoptosis is an immune regulatory mechanism, and DC-derived EVs with TNF, FasL and TNF related apoptosis inducing ligand (TRAIL) can activate natural killer cells, and induce tumor cell apoptosis (Munich et al, 2012 ), and could also play a role in systemic inflammation.…”
Section: Lung Evs In Non-pulmonary Disordersmentioning
confidence: 99%
“…Platelets are activated in MS and have been implicated in contributing to MS pathogenesis, such as by promoting inflammation [26, 35]. Our results demonstrate, that the activation of platelets from SP MS patients is significantly raised compared to platelets from healthy subjects, and observed differences are directly related to the COX activation.…”
Section: Discussionmentioning
confidence: 52%
“…Some reports emphasize the importance of platelet activation in MS [35]. Our previous studies also clearly demonstrated that blood platelets are chronically activated in the circulation of SP MS patients [36].…”
Section: Discussionmentioning
confidence: 69%
“…Additionally, we included 25 publications that fulfilled inclusion criteria but were found otherwise. Final analysis was performed on 65 publications (Fig. ).…”
Section: Designmentioning
confidence: 99%